Nitric oxide biosynthesis during normal pregnancy and pregnancy complicated by preeclampsia - Jasmin Hodžić; Sebija Izetbegović; Bedrana Muračević; Rasim Iriškić; Hana Štimjanin Jović (Medicinski glasnik, 2017)
Aim: To investigate biosynthesis in nitric oxide (NO) during normal pregnancy and in pregnancies complicated by preeclampsia. Methods: This prospective cross-sectional study included 80 patients hospitalized at the Department of Women's Health, Neonatology and Perinatology Cantonal Hospital in Zenica. Serum NO concentration in 20 non-pregnant women, 40 healthy pregnant women and 20 pregnant women with preeclampsia aged 17-40 years were measured. The group of healthy pregnant women were divided into 4 subgroups by gestational age. For each woman with preeclampsia, a healthy pregnant control was matched for age, parity and gestational age. Serum NO concentrations were determined after reduction of nitrates to nitrites using the Griess reaction. Results: NO concentrations during second trimester of pregnancy (37.2±1.7µM; p<0.05) and third trimester of pregnancy (40.9±2.8?M; p<0.05) were significantly higher in healthy pregnant women than in non-pregnant women (29.3±1.7?M). Serum NO concentrations were lower in preeclamptic women (30.7±1.8?M) compared to matched healthy pregnant women of the third and the late third trimester (35.1±2.2?M), without significant differences. Mean NO concentrations in pre-eclamptic women was positively correlated with systolic blood pressure (r=0.58; p<0.01), diastolic blood pressure (r=0.45; p<0.05), creatinine clearance (r=0.48; p<0.05), uric acid (r=0.49; p<0.05), and negatively correlated with platelet count (r=-0.57; p<0.05). Conclusion: NO production was increased with gestational age during normal pregnancy and slightly decreased in preeclampsia suggesting that NO may modulate the cardiovascular changes during normal pregnancy and pregnancy complicated by preeclampsia.
Keywords: pathogenesis; vasoconstriction; hypertension; pregnancy complications